2011
DOI: 10.1021/es103534g
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Partial and Full Nitrification Processes Applied for Treating High-Strength Nitrogen Wastewaters: Microbial Ecology through Nitrous Oxide Production

Abstract: The increasing regulatory demands to achieve greater nutrient removal from wastewater treatment plant effluents, while minimizing infrastructure investments and operating costs, has resulted in the development of several innovative biological nitrogen removal (BNR) processes. Partial nitrification based processes such as the single reactor system for high ammonium removal over nitrite (SHARON 1 ) and its variants are attractive for treating high-strength nitrogen waste streams such as anaerobic digestion rej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
77
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 125 publications
(91 citation statements)
references
References 36 publications
12
77
2
Order By: Relevance
“…The application of rRNA-based assays to detect active bacteria has proven useful in several studies (18)(19)(20)(21). In a previous study, we demonstrated that the detection frequency of rRNA-based assays were in better agreement with the culture based detection of E. coli and enterococci in surface waters than that of rRNA genebased assays, suggesting that rRNA signals were associated to active bacterial populations (27).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The application of rRNA-based assays to detect active bacteria has proven useful in several studies (18)(19)(20)(21). In a previous study, we demonstrated that the detection frequency of rRNA-based assays were in better agreement with the culture based detection of E. coli and enterococci in surface waters than that of rRNA genebased assays, suggesting that rRNA signals were associated to active bacterial populations (27).…”
Section: Discussionmentioning
confidence: 77%
“…These results demonstrate that targeting rRNA via RT-qPCR may provide up to 1,000-fold greater sensitivity over corresponding rRNA gene targets. Indeed, the higher sensitivity of RT-qPCR technique compared to qPCR have been reported for quantification of bacteria in natural and engineered systems such as human gut (28), marine sediments and grasslands (50,51), environmental waters (27), and activated sludge processes (21,52). Thus, in our study, the increased detection of fecal bacteria markers via rRNA-based signals suggests that RT-qPCR assays may be better suited for tracking and quantifying active fecal bacteria in environmental waters when the targeted groups are present at relatively low levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different characteristics of AOB and NOB have been studied in order to develop strategies for NOB control in partial nitritation systems. These are based on temperature, dissolved oxygen, hydraulic retention time (HRT) and solid retention time (SRT), or free ammonia (FA) and free nitrous acid (FNA) concentrations, among others [14,24,35,36]. When 50% ammonium is oxidized under steady-state conditions, partial nitritation reactors have a relative abundance of 64% AOB and less than 5% NOB [37].…”
Section: -80mentioning
confidence: 99%
“…Higher nitrous oxide concentrations in the samples were located at the root zone in all the lysimeters. An example of the results from lysimeter 3 (L3), watered with a nitrogen fertilizer solution, is shown in Table 2 ( Ahn et al, 2011).…”
Section: Resultsmentioning
confidence: 99%